The Effect of Total Liabilities and Operating Expenses on Net Income: Evidence from Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange - Revina Nanda Octavia; Bella Puspita Rininda; Widiya Astuti Alam Sur; Astia Putriana; Mufrida Zein (Jurnal Penelitian Ekonomi dan Akuntansi JPENSI, 2026)
This study aims to examine the effect of total liabilities and operating expenses on net profit in manufacturing companies, particularly those in the food and beverage subsector listed on the Indonesia Stock Exchange during the 2019–2023 period. The analysis employs multiple linear regression using 80 observations obtained from 16 companies. The results indicate that total liabilities have a positive effect on net profit, while operating expenses do not show a significant effect. In addition, the simultaneous test (F-test) reveals that all variables jointly influence net profit. The coefficient of determination (R²) of 0.622 indicates that 62.2% of the variation in net profit can be explained by total liabilities and operating expenses, while the remaining 37.8% is influenced by other factors outside the model used in this study.